Efficient lanthanide Gd doping promoting the thermoelectric performance of Mg3Sb2-based materials. Issue 46 (3rd November 2021) - Lei, Jingdan; Wuliji, Hexige; Zhao, Kunpeng; Wei, Tian-Ran; Xu, Qing; Li, Peng; Qiu, Pengfei; Shi, Xun
Abstract : By considering the electronegativity difference and mass difference between dopant and host elements, we theoretically and experimentally demonstrated Gd as an effective dopant to promote thermoelectric performance of Mg3 Sb2 -based materials. Abstract : Mg3 Sb2 -based thermoelectric materials have recently received heightened attention due to their diverse merits of high band degeneracy, ultralow lattice thermal conductivity and high carrier mobility. However, the inherently low carrier concentration of pristine Mg3 Sb2 seriously hinders the advancement of this material toward high thermoelectric performance. Therefore, searching for proper dopants to optimize the carrier concentration is one of the primary avenues to realize superior thermoelectric performance in Mg3 Sb2 -based materials. Herein, by considering the electronegativity difference Δ χ and mass difference Δ M between the dopant and host elements, we theoretically and experimentally demonstrate lanthanide Gd as an effective dopant to tune the carrier concentration of Mg3 Sb1.3 Bi0.7 alloys. Owing to its high doping efficiency, a large carrier concentration up to 8.9 × 10 19 cm −3 is realized through Gd doping, which is close to the optimal value. Moreover, the coarse grain size commendably mitigates the grain boundary effects and thus ensures high carrier mobility. Combining the greatly suppressed lattice thermal conductivity by point defect scattering, a maximum zT of 1.55 is achieved at 700 K in Mg3.065 Sb1.3 Bi0.7 Gd0.015 .